Educational challenges for 22q11.2 deletion syndrome in Japan: Findings from a mixed methods survey. Issue 3 (13th February 2023) - Tanaka, Miho; Kanehara, Akiko; Morishima, Ryo; Kumakura, Yousuke; Okouchi, Noriko; Nakajima, Naomi; Hamada, Junko; Ogawa, Tomoko; Tamune, Hidetaka; Nakahara, Mutsumi; Jinde, Seiichiro; Kano, Yukiko; et al.
Abstract: Background: The 22q11.2 deletion syndrome (22q11DS) is characterised by a changing pattern of overlapping intellectual, physical, and mental disabilities along the course of one's life. However, the impact of overlapping disorders (multimorbidity) on educational challenges remains unclear. Method: A survey was conducted with 88 caregivers of individuals with 22q11DS. A quantitative analysis of educational challenges and support needs divided into age groups (7–12, 13–15, 16–18, and 19 years and over) and a qualitative analysis of the free‐text items in the questionnaire was conducted. Results: Caregivers were more interested in comprehensive developmental support when their children were younger, and the emphasis shifted to concerns regarding environments that matched individual characteristics at older ages. Furthermore, when there are multiple disabilities or disorders, support is concentrated on the more obvious disabilities, and the lack of support for the less superficially obvious disabilities associated with multiple difficulties, including mental health problems, can be a challenge for people with 22q11DS and their families. Conclusions: This study suggests a need for increased focus on multimorbidity and associated disabilities in school education that are difficult to observe because of their mildness or borderline levels if present alone.